Menilai Perkembangan Motorik Kasar Anak Melalui Permainan Lompat Tali - Ferasinta Ferasinta; Padila Padila; Rahma Anggita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effect of rope jumping games on gross motor skills in children. This study uses a Quasy Experiment research design with a One Group Pre-Post Design approach. The results of this study show the effect of jumping rope on gross motor development in children with pre-test and post-test data of jumping rope with p-value = 0.001. In conclusion, rope jumping games affect gross motor development in children because rope jumping games have jumping movements in a balanced and coordinated manner. Keywords: Jumping Rope, Jumping, Gross Motor